False-Negative Rate of Papanicolaou Testing: A National Survey from the Thai Society of Cytology - Supinda Koonmee (2018)
© 2017 S. Karger AG, Basel. Copyright: All rights reserved. Objective: To evaluate the performance of Papanicolaou smear screening in Thailand at the national level, and to propose recommendations for continuing quality control. Study Design: This study was conducted by The Thai Society of Cytology and involved 124 laboratories in 76 provinces during 2010-2014. Random sampling suggested recalling of 10% of slides defined as negative at routine screenings (10% random rescreening [R10] model) directly from the reading unit. Results: Out of 330,075 smears covered by the rescreening project throughout its 5-year duration, the rates of abnormal, unsatisfactory, and normal results were 0.63, 1.82, and 97.55%, respectively. Abnormal findings were largely represented by ASC-US (54%) and L-SIL (21%). The average false-negative rate (FNR) measured at the level of L-SIL and higher was 13.8%. Conclusion: The national project was developed to address the accuracy of cervical cancer screening and to promote internal quality assurance based on the R10, on-site surveys, and education. The major output parameters of this study (FNR and number and distribution of abnormal cases on rescreening) improved significantly in the main phase of the project (2012-2014), after revising substantial logistics issues encountered during the first 2 years of this study. This project provided objective measurable evidence related to the quality of cytology-based cervical cancer screening in Thailand.